Hubungan Karakteristik Ibu dengan Status Gizi Balita di Desa Baumata Timur Kecamatan Taebenu Kabupaten Kupang - Agustina Setia (Kupang Journal of Food and Nutrition Research, 2021)
Background: Nutritional Disorders in toddlers can be affected by several factors, both directly and indirectly. Several factors are maternal characteristics. This study aims to determine the relationship between maternal characteristics and nutritional status of children under five in Baumata Timur. Methods: The study used a descriptive analytic method with cross sectional, population 952. Sampling used Proportional Stratified Random Sampling. Data were collected by using physical measurements and questionnaires. The sample is 43 people. Data analysis used Spearman rank correlation. Results: There is a relationship between the mother's education with infant nutritional status (p = 0.000). There is a relationship between mother parity with nutrition status (p = 0.000). There is a relationship between the level of knowledge of mothers about nutrition with nutritional status (p = 0.000). Conclusion: There is a relationship between education, parity, and the level of knowledge of mothers about nutrition with nutritional status of children. Keywords: education, parity, knowledge, nutritional status